2014
DOI: 10.1155/2014/310626
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic System for Speed-Varying Motor Rotary Faults

Abstract: This study proposed an intelligent rotary fault diagnostic system for motors. A sensorless rotational speed detection method and an improved dynamic structural neural network are used. Moreover, to increase the convergence speed of training, a terminal attractor method and a hybrid discriminant analysis are also adopted. The proposed method can be employed to detect the rotary frequencies of motors with varying speeds and can enhance the discrimination of motor faults. To conduct the experiments, this study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The time available for initiating a maintenance action before a catastrophic failure after confirming a defect will be very short if this traditional technique is used. In contrast, Tseng, et al [18] and Kamiel, et al [19] have shown that utilizing the statistical process control (or statistical control chart) techniques combined with the time-domain features have effectively improved the fault detection process, but could not diagnose it. Thus, as it was mentioned previously that the first stage is in charge of only detecting the fault, so the combination of time-domain signal analysis with SCC will be applied at this stage.…”
Section: Time-domain Signal Analysis Techniquementioning
confidence: 98%
“…The time available for initiating a maintenance action before a catastrophic failure after confirming a defect will be very short if this traditional technique is used. In contrast, Tseng, et al [18] and Kamiel, et al [19] have shown that utilizing the statistical process control (or statistical control chart) techniques combined with the time-domain features have effectively improved the fault detection process, but could not diagnose it. Thus, as it was mentioned previously that the first stage is in charge of only detecting the fault, so the combination of time-domain signal analysis with SCC will be applied at this stage.…”
Section: Time-domain Signal Analysis Techniquementioning
confidence: 98%